Phenotypic bases of NOTCH2NLC GGC expansion positive neuronal intranuclear inclusion disease in a Southeast Asian cohort. Issue 3 (26th July 2020) - Chen, Zhiyong; Xu, Zheyu; Cheng, Qianhui; Tan, Yi Jayne; Ong, Helen L.; Zhao, Yi; Lim, Weng Khong; Teo, Jing Xian; Foo, Jia Nee; Lee, Hwei Yee; Tan, Jeanne M.M.; Hang, Liting; et al.
Abstract: Neuronal intranuclear inclusion disease (NIID) is a neurodegenerative disorder associated with GGC repeats of >60 to 500 copies in the 5′‐untranslated region of NOTCH2NLC . The clinical and genetic characterization of NIID outside of East Asia remains unknown. We identified twelve patients who underwent genetic testing using long‐read sequencing or repeat primed polymerase chain reaction. All were positive for a GGC repeat expansion; the median repeat length was 107 (range 92‐138). Ten were Chinese and two of Malay ethnicity. Age at onset ranged from 50 to 69 years. Eight (66.7%) patients had dementia, while four (33.3%) patients were oligosymptomatic, without typical NIID symptoms of dementia, Parkinsonism, or muscle weakness. GGA interruptions within the GGC expansion were present in four patients; the number of GGA interruptions was highest (6.71%) in the patient with the earliest age at onset (50 years). Median plasma neurofilament light level was 47.3 pg/mL in seven patients (range 26‐380 pg/mL). The highest level (380 pg/mL) was found in one patient who experienced an encephalitic episode. Overall, we describe a cohort of genetically confirmed NIID patients from Southeast Asia and provide further information that the presence of GGA interruptions within GGC repeat expansions may serve as a potential genetic modifier in NIID. Abstract : The presence of characteristic MRI Brain features of Neuronal Intranuclear Inclusion Disease (NIID) predicts the presence of NOTCH2NLC GGC repeat expansions in patients with a broad phenotypic spectrum